A Set of Hands-On Exercises on Conformational Analysis - Pellegrinet, Silvina Carla (2005)
This article describes a set of comprehensive exercises on conformational analysis that employs a hands-on approach by the use of molecular modeling kits. In addition, the exercises provide illustrations of other topics such as nomenclature, functional groups, and isomerism, and introduce some notions of chirality.